PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA GURU - Simanungkalit, Eva Marlina (Equity In Education Journal, 2025)
This study aims to analyze the influence of transformational leadership and motivation on the performance of public elementary school teachers in Kertak Hanyar District, Banjar Regency. The approach used is quantitative with a path analysis model. The research population consists of 150 teachers from 17 public elementary schools, with a sample of 110 teachers selected using proportional random sampling. The validity of each variable's questionnaire was tested using the Product Moment Correlation, while reliability was tested using Cronbach's Alpha formula. Data was collected through a questionnaire consisting of variables related to the principal's transformational leadership (41 items), work motivation (32 items), and teacher performance (24 items). Before testing the hypotheses, the data were first tested for prerequisites through normality and linearity tests, then analyzed using path analysis. The results of the study indicate a direct influence of transformational leadership and motivation on teacher performance, as well as an indirect influence of transformational leadership on teacher performance through motivation.